PENOLAKAN PEMBATALAN MEREK DIAKIBATKAN DALUWARSA ANTARA PENGADILAN NIAGA DAN MAHKAMAH AGUNG DITINJAU DARI UNDANG-UNDANG NO. 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS. (STUDI KASUS PUTUSAN PENGADILAN NIAGA NO. 44/PDT.SUS.MEREK/2019/PN.NIAGA.JKT.PST Jo. PUTUSAN MAHKAMAH AGUNG NO. 794 K/PDT.SUS-HKI/2020) - Jesslyn Evelina Tandrajaya; R Rahaditya (Jurnal Hukum Adigama, 2021)
Intellectual Property Rights are exclusive rights obtained from intellectual works created or discovered or created by humans. One type of Intellectual Property Rights is trademark. Trademarks must be registered, because their registration creates an exclusive and absolute right to the trademark. Exclusive rights can be interpreted that these rights can be maintained by the holder or the owner of the trademark. But in reality, it is still found that there are similar brand similarities between one brand and another. Trademarks can be filed for cancellation which has been regulated in Act no. 20 of 2016 concerning Trademark and Geographical Indications. However, regarding the cancellation of the trademark, there is a limitation that the trademark can only be canceled for 5 years from the time the brand is registered, beyond that the cancellation of the trademark can be said to have expired. The cancellation of the trademark can be carried out indefinitely if the trademark is found to have elements of bad faith. Expiration is a tool to obtain or free oneself from a certain engagement. The method used in this research is normative legal research. The results of the research obtained are that in deciding cases each judge has a different view, as in the case of judges having different views regarding expiration. Judges of the Commercial Court use expiration as the basis for rejecting the lawsuit for trademark cancellation, while Judges of the Supreme Court use that bad faith can override expiration.